Prevalence and risk factors of intestinal Helminthiasis among the children of Begun Bari slum, Tejgaon, Dhaka - Mukutmoni, Mandira; Khanum, Hamida (Bangladesh Journal of Zoology, 2018)
A cross sectional parasitological study was conducted among the underprivileged children of Begun Bari slum, Tejgaon, Dhaka during January 2015 to December 2016. Fecal samples were collected and then processed through formaldehyde-ether concentration technique. Prevalent helminths were Ascaris lumbricoides (27.68%), Trichuris trichiura (21.57%) and Taenia saginata (18.24%). Male children were at high risk for helminth infection than females. The highest prevalence of A. lumbricoides (42.11%) was observed among the children aged 10 -12 years and T. saginata (35.71%) among 13 - 15 years. The prevalence of A. lumbricoides (23%) was the uppermost in the winter (23%) and the lowest in the rainy season (4.3%). Children of illiterate mothers (91.89%), bare footers (76.03%) and mud floor residents (76.43%) were more prone to helminth infections (p < 0.05). Bangladesh J. Zool. 45(2): 123-129, 2017